2017
DOI: 10.1287/mnsc.2016.2449
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrations and Price Competition in New Product Release

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Hence one explanation for the Huawei's practice is that, before the release of the smartphone, the extent of ex-ante product information perceived by consumers is relatively low, hence Huawei adopts a relatively high proportion of prepayment. With the increase of extent of ex-ante product information due to information sharing between consumers [30], Huawei decreases the prepayment proportion.…”
Section: Corollary 7 the Retailer's Profit In The Map Scenario Has Fmentioning
confidence: 99%
“…Hence one explanation for the Huawei's practice is that, before the release of the smartphone, the extent of ex-ante product information perceived by consumers is relatively low, hence Huawei adopts a relatively high proportion of prepayment. With the increase of extent of ex-ante product information due to information sharing between consumers [30], Huawei decreases the prepayment proportion.…”
Section: Corollary 7 the Retailer's Profit In The Map Scenario Has Fmentioning
confidence: 99%
“…Thus, in this paper, the sales effort we discuss mainly refers to the various marketing means adopted by the retailer in its offline physical stores to increase sales, such as whether the retailer's investment in the display of the products sold includes all types, styles and colors for consumers to experience and whether the function demonstration and introduction of the products by the sales staff of the physical store are specific and clear. Several studies [73][74][75] have shown that this kind of sales effort to increase consumer experience or deepen consumer understanding of a product can increase its purchase utility and have a direct impact on its purchase decision. We assume that the sales effort of the retailer in physical stores is s , and the corresponding effort cost function is represented as Similar to He, et al [79] and Feng, et al [8], we assume that there are two types of consumers in the market, namely, traditional consumers and online consumers.…”
Section: Problem Description and Notationmentioning
confidence: 99%
“…They consider that the retailer's choice of refusing returns can help eliminate the manufacturer's incentive to induce inefficient consumer returns. Boleslavsky, Cotton, and Gurnani (2017) explore an innovative firm's product demonstration strategy when facing a competitor who offers an established product. They find that the innovative firm should fully disclose product information when prices respond to the demonstration policy, but when the innovative firm can adjust its demonstration strategy in response to prices, he prefers a partially informative demonstration.…”
Section: Literature Reviewmentioning
confidence: 99%